Genome Sequence of Escherichia coli O157:H7 Strain 2886-75, Associated with the First Reported Case of Human Infection in the United States - Sanjar, Fatemeh (American Society for Microbiology, 2014)
First identified in 1982 as a human pathogen, enterohemorrhagic Escherichia coli of the O157:H7 serotype is a major cause of food-borne acquired human infections. Here, we report the genome sequence of the first known strain of this serotype isolated in the United States.